Pendampingan Dalam Meningkatkan Kualitas Baca Al-Qur'an Dengan Metode Iqro di TPQ Riadhul Badi’ah Dusun Biletepung Desa Beleka - Sudirman; Syamsul Hadi; Samsul Hakim; Alfan Hadi; Santi Apriana; Lisa Prahayuningsih; Liza Azrianti; Ma'ani; Shopiatun Rudiah; Seri Wahyuni; Suhartini; Ahmad Syukron; Yunus Hidayatullah; Yuliani (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2025)
The majority of the people in Bilatepung Hamlet work as farmers and traders in addition to their profession as teachers, where they spend their time leaving in the morning and returning in the afternoon and resting at night. This makes the time for children to be assisted less in the process of learning to read and write the Qur'an. There are still many children in Bilatepung Hamlet who still cannot read and write the Qur'an. Therefore, reading and writing assistance is carried out at TPQ Riadhul Badi'ah. At TPQ Riadhul Badi'ah Assistance in Improving the Quality of Reading the Quran Using the Iqro' Method, where this method is an effective method used for early childhood, the iqro' method is complemented by practical and relatively short tajweed books. This method emphasizes reading with fashih and correct according to the makhroj. The method used in conducting this research is by using the Participatory Active Research (PAR) method. Data collection used is direct observation by taking some documentation. The results of this study, with the assistance can improve the ability of TPQ children in reading and writing al qu'an. It can be seen the motivation of TPQ children in reading the Qur'an properly and correctly.